1981
DOI: 10.1007/bf00051769
|View full text |Cite
|
Sign up to set email alerts
|

Ecological outbreak dynamics and the cusp catastrophe

Abstract: Abstract. Many ecological processes exhibit trajectories which can be suitably represented by stable equilibria or smooth limit cycles. However, a third kind of ecological process involves intermittent, abrupt, and drastic changes in densities, here termed 'outbreak dynamics', which require different modelling frameworks. One such framework, the cusp catastrophe, is used here in a modelling study of a particular outbreak insect, the forest tent caterpillar. This model is then generalized to cover a set of rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…Insect outbreaks (Harmsen et al, 1976;Ludwig et al, 1978;Rose & Harmsen, 1981) and transitions between clear and turbid states in shallow lakes (Scheffer, 1990;Scheffer et al, 1993) are known to be good examples for the application of the catastrophe theory in ecology. Our model has suggested that the catastrophe theory is also applicable to the vertical pattern formation of phytoplankton especially when there exists a well-defined seasonal thermocline.…”
Section: Applicability Of Catastrophe Theory For Vertical Distributiomentioning
confidence: 98%
“…Insect outbreaks (Harmsen et al, 1976;Ludwig et al, 1978;Rose & Harmsen, 1981) and transitions between clear and turbid states in shallow lakes (Scheffer, 1990;Scheffer et al, 1993) are known to be good examples for the application of the catastrophe theory in ecology. Our model has suggested that the catastrophe theory is also applicable to the vertical pattern formation of phytoplankton especially when there exists a well-defined seasonal thermocline.…”
Section: Applicability Of Catastrophe Theory For Vertical Distributiomentioning
confidence: 98%
“…1989; Bazely & Jefferies 1996; Rietkerk & Van de Koppel 1997). When vegetation change is a non‐linear process with apparent discontinuities (Rose & Harmsen 1981), or a series of threshold responses between meta‐stable states (Westoby et al . 1989; Rietkerk & Van de Koppel 1997), restoration efforts require knowledge of the various variables that need to be manipulated in order to achieve state transitions (Hobbs 1994; Hobbs & Norton 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Large-scale outbreaks and similar oscillations, particularly of pest species, are seen as undesirable, in part because of their economic implications. This is the context of papers by Jones (1977), Rose and Harmsen (1981) and Casti (1982). The last, relating (as does Jones' analysis) to the spruce budworm, is notable for its conclusion that the sought-for goal is not always attainable.…”
Section: Ecological Studiesmentioning
confidence: 99%